2015
DOI: 10.1177/1535370215605586
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β-sphingosine kinase 1/S1P signaling upregulates microRNA-21 to promote fibrosis in renal tubular epithelial cells

Abstract: Renal fibrosis is a progressive pathological change characterized by tubular cell apoptosis, tubulointerstitial fibroblast proliferation, and excessive deposition of extracellular matrix (ECM). miR-21 has been implicated in transforming growth factor-b (TGF-b)-stimulated tissue fibrosis. Recent studies showed that sphingosine kinase/sphingosine-1-phosphate (SphK/S1P) are also critical for TGF-b-stimulated tissue fibrosis; however, it is not clear whether SphK/S1P interacts with miR-21 or not. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
2
22
0
1
Order By: Relevance
“…Several studies have demonstrated that miR-21 level is elevated in lung tissues from PAH patients and mice PAH models [29], and miR-21 up-regulation contributes to pulmonary vascular remodeling via promoting PASMC proliferation in the pathogenesis of PAH [30,31]. Liu et al have found that SphK1/S1P pathway increases miR-21 expression to promote fibrosis in renal tubular epithelial cells [32]. Degagné et al have further demonstrated that signal transducer and activator of transcription 3 (STAT3) medicates S1P-induced upregulation of miR-21 in colonic epithelial cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that miR-21 level is elevated in lung tissues from PAH patients and mice PAH models [29], and miR-21 up-regulation contributes to pulmonary vascular remodeling via promoting PASMC proliferation in the pathogenesis of PAH [30,31]. Liu et al have found that SphK1/S1P pathway increases miR-21 expression to promote fibrosis in renal tubular epithelial cells [32]. Degagné et al have further demonstrated that signal transducer and activator of transcription 3 (STAT3) medicates S1P-induced upregulation of miR-21 in colonic epithelial cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, two of the most upregulated miRNAs observed in patients with active EoE, miR-21 and miR-223, have been shown to have functions that would support a pathologic role in EoE. miR-21 is implicated in eosinophil survival, allergic inflammation, and TGF-β-stimulated tissue fibrosis [6163]. Similarly, miR-223 has been implicated in regulating IL-5 expression and eosinophil development [64].…”
Section: Genetics Epigenetics and Transcriptional Analysesmentioning
confidence: 88%
“…Inflammation is an important contributor to cholestasis‐induced liver injury . S1P and S1PRs have been identified as key players in various fibrotic diseases, including LF . Recent studies reported that S1PR2/3‐mediated homing of bone‐marrow–derived immune cells contributes to cholestasis‐induced liver fibrosis .…”
Section: Discussionmentioning
confidence: 99%